2021
DOI: 10.1080/21655979.2021.1960130
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar protein NOP2 could serve as a potential prognostic predictor for clear cell renal cell carcinoma

Abstract: As an indispensable part for cancer precision medicine, biomarkers and signatures for predicting cancer prognosis and therapeutic benefits were urgently required. The purpose of this study was to investigate the prognostic roles of NOP2 in renal clear cell carcinoma (ccRCC) for overall survival (OS) and its relationships with immunity. NOP2-related gene expression matrix associated with clinical information was obtained from the Cancer Genome Atlas (TCGA) ccRCC dataset and NOP2-related pathways were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…A trend was also observed that the later the tumor stage, the higher the expression of NOP2, especially in ACC and KIRC. Consistent with our results, Wang et al (2021 ) demonstrated significant associations between high NOP2 expression and age and tumor stage in KIRC. However, NOP2 expression was not related to age, gender, and tumor stage in resected LUAD, which was not in accordance with our study ( Sato et al, 1999 ).…”
Section: Discussionsupporting
confidence: 91%
“…A trend was also observed that the later the tumor stage, the higher the expression of NOP2, especially in ACC and KIRC. Consistent with our results, Wang et al (2021 ) demonstrated significant associations between high NOP2 expression and age and tumor stage in KIRC. However, NOP2 expression was not related to age, gender, and tumor stage in resected LUAD, which was not in accordance with our study ( Sato et al, 1999 ).…”
Section: Discussionsupporting
confidence: 91%
“…A 12-gene signature related to iron metabolism was developed in lung cancer [ 87 ]. NOP2 expression was found to be related to stage, age, grade and prognosis in RCC [ 88 ]. HSF1 was observed upregulated in multiple cancers and might be a potential target for immunotherapy [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…We detected a high NOP2, also known as NSUN1, mRNA level in PRAD samples which ties well with previous findings. The amplification of NOP2 and its overexpression is frequently found in renal cell carcinoma (RCC) [52]. Increased NOP2 expression in diverse cancer types such as LUAD, LUSC, adrenocortical carcinoma, and ovarian serous cystadenocarcinoma was described in a reported pan-cancer study [53].…”
Section: Discussionmentioning
confidence: 99%